Normalization strategies for real-time expression data in Chlamydia trachomatis - Borges, V. (2011)
Chlamydia trachomatis is a widespread obligate intracellular pathogen genetically non-tractable for which transcriptomics is a fundamental tool to better understand its biology. However, the suitability of endogenous controls for normalization of transcriptomic data in this bacterium still needs validation. We aimed to assess the stability of 10 genes for their potential use as endogenous controls in real-time quantitative PCR assays at both normal and stress (D-cycloserine treatment) growth conditions throughout the developmental cycle of three C. trachomatis strains with different tissue tropism. Normalization was performed by real-time absolute quantification of the bacterial genomes. We also tested the applicability of two widely used softwares (geNorm and Normfinder) to our data. For all strains, we found that 16SrRNA was the most stably expressed gene throughout the chlamydial normal developmental cycle, which indicates its potential use as endogenous control in relative expression assays. However, it was highly unstable under D-cycloserine treatment (where oppA_2 was top-ranked), suggesting prudence when using ribosomal genes in expression experiments involving stress conditions. The geNorm and Normfinder algorithms revealed contrasting results and seem inappropriate for the selected pool of genes. Considering the multiplicity of experimental conditions, there should be an in loco validation of endogenous controls, where 16SrRNA appears to be in the front line. Alternatively, normalization of expression data against genomic DNA, which is less influenced by experimental constraints that are especially relevant for intracellular organisms, likely constitutes a good option. Moreover, the number of genomes also seems to be less subject to variation than expression of endogenous controls when working under stress conditions. The present study constitutes the first evaluation of putative endogenous controls for real-time expression assays in C. trachomatis.